The Hashtags and Digital Opinion Movements: A Social Network Analysis of the #BubarkanPSSI Hashtag - Indra Jaya Sihombing (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2023)
Conversations using the hashtag #BubarkanPSSI is a Digital Opinion Movement that highlights the existence of PSSI as the management of national football. The purpose of this research is to map the network structure formed in the conversations of netizens using #BubarkanPSSI on Twitter social media. The concept used in this research is the Digital Opinion Movement which describes and explains social networks and their network structures. The method used in this research is the Social Network Analysis (SNA). This research focuses on Twitter user conversations using the hashtag #BubarkanPSSI in the period 9-16 October 2022 which was downloaded using Netlytic. The results showed that there were 562 actors involved with a total of 706 interactions. Interaction between actors occurs easily but the connection between actors looks low and the communication that occurs is one-way. There is no one actor who dominates so the conversation is decentralised where information flows more freely among the actors involved. The keywords that emerged during the conversation period studied placed PSSI as an institution that was considered a failure and should be disbanded. PSSI needs to pay more attention to the keywords that appear in the conversation because the netizen opinions that arise in the conversation reflect the negative views of the public towards the reputation of PSSI.